Analyzing Innovation Capability of some Enterprises Operating in the Agricultural Sector in Vietnam: Case of 3 Firms - Quoc Hung, Nguyen; Ngoc Ca, Tran; Thanh Tung, Dang (VNU Journal of Science: Policy and Management Studies, 2025)
This study synthesizes and proposes a concept and a method for evaluating the innovation capability of enterprises, specifically applying it to several enterprises in the agricultural value chain. The authors propose a method that combines different approaches to assessing innovation capability based on the method of Joe Tidd, John Bessant, as well as Hoang Dinh Phi and Hoang Anh Tuan. The indicators used to evaluate a company's innovation capability were analyzed and include: i) Strategy; ii) Process; iii) Organization; iv) Linkages; v) Learning; and vi) Technology. These comprehensively represent the two main groups of capabilities: technological capability and management capability. The research results indicate that it is feasible to combine these indicators into a unified model for assessing and analyzing a company's innovation capability. This method can reveal the current state of innovation capability in businesses, at least within the agricultural value chain. Besides the achievements, this method requires further research to overcome certain limitations in its methodology and data.